Preparation method of ultra-low refractive index and high-transparency cycloolefin copolymer

Through the polymerization of cycloolefin monomers and fluorine-containing cycloolefin monomers promoted by Grubbs catalyst, a cycloolefin copolymer with high fluorine-containing and amorphous structure was prepared, solving the crystallinity and cost problems of cycloolefin polymers in the field of antireflective films. , achieving ultra-low refractive index and high transparency, improving material compatibility and interface adhesion.

CN119241814AActive Publication Date: 2025-01-03TIANJIN UNIV

Patent Information

Application Number
CN202411601246.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-03
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The application of existing cycloolefin polymers in the field of antireflective films is limited by their crystallinity and high cost, and it is difficult to achieve a highly transparent and amorphous structure in large-scale production of low refractive index materials.

Method used

The ring-opening metathesis polymerization reaction of cycloolefin monomer and fluorine-containing cycloolefin monomer in organic solvents was performed using Grubbs catalyst, and a cycloolefin copolymer with high fluorine-containing and amorphous structure was prepared through hydrogenation reaction, achieving ultra-low Refractive index and high transparency.

Benefits of technology

Amorphous cycloolefin copolymer with high fluorine content, ultra-low refractive index (1.37-1.47 adjustable), high transparency and good solubility in conventional solvents were obtained, which improved the compatibility of the anti-reflective coating and the matrix material. and interface adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241814A_ABST
    Figure CN119241814A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an ultralow-refractive-index and high-transparency cycloolefin copolymer, and belongs to the technical field of polymer preparation, the method comprises the following steps: in the presence of a Grubbs catalyst and an organic solvent, carrying out ring-opening metathesis polymerization reaction on a cycloolefin monomer and a fluorine-containing cycloolefin monomer to obtain the ultralow-refractive-index and high-transparency cycloolefin copolymer. The unsaturated fluorine-containing cycloolefin copolymer is prepared; and carrying out hydrogenation reaction on the unsaturated fluorine-containing cycloolefin copolymer and a hydrogen source to obtain the fluorine-containing cycloolefin copolymer. The fluorine-containing cycloolefin copolymer prepared by the method disclosed by the invention has the excellent properties of ultralow refractive index, high transparency, high thermal stability, excellent mechanical property, amorphous form and the like, and the refractive index is adjustable in a range of 1.37-1.47; the ultralow refractive index is far lower than that of the conventional typical organic low-refractive-index commercial material PMMA (the refractive index is 1.49). Therefore, the fluorine-containing cycloolefin copolymer prepared by the method can be widely applied to the optical field, such as low-refractive-index optical lenses (AR and VR glasses), anti-reflection coatings and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer preparation, and in particular relates to a method for preparing an ultra-low refractive index and highly transparent cycloolefin copolymer. Background Art

[0002] Cycloolefin polymers are a type of high-value-added thermoplastic engineering plastics polymerized from cycloolefin monomers. They have excellent comprehensive properties, such as high transparency, low birefringence, low dielectric constant, and good dimensional stability. Therefore, cycloolefin polymers have broad application prospects in the fields of mobile phone lenses, VR lenses, etc. However, with the rapid development of multimedia technology, people have put forward higher requirements for image acquisition and recording of high-quality images. Therefore, reducing the reflection of light on the display surface of the image receiving device can effectively improve the image collection quality. At present, in order to reduce the reflection of the display surface, it is usually necessary to perform anti-reflection treatment on the display surface, and the commonly used technical means for anti-reflection include: 1. Coating inorganic materials such as silicon dioxide and magnesium fluoride on the plastic surface; 2. Constructing micro-nano structures on the surface; 3. Low-refractive polymer coating. Inorganic materials have poor compatibility with the substrate, and the risk of particle peeling is relatively high; micro-nano structure construction usually has high equipment requirements, cumbersome production, and poor stability of material properties; and low-refractive polymers are suitable for matching the refractive index of different substrates due to their low cost, lightweight and adjustable molecular structure in large-scale production. Anti-reflective polymer films (AR films) are usually composed of alternating high-refractive polymer layers and low-refractive polymer layers. In recent years, its application in the fields of displays, lens materials, etc. has become increasingly important. In AR films used in the optical field, in addition to requiring low refractive index, high Abbe number, and low reflectivity (1.5% or lower), the film is also required to have strong compatibility with the substrate material to ensure the adhesion strength of the coating. In addition, in addition to the requirements of low refractive index and high Abbe number, the amorphous structure of the polymer is also crucial for anti-reflective materials. Since the shrinkage rate of the crystalline polymer during molding is large, there are amorphous parts and crystalline parts coexisting in the molded products, resulting in irregular reflections. Therefore, even if the crystalline polymer has a lower refractive index (such as poly-4-methyl-1-pentene, refractive index 1.46), it is not suitable for applications in the fields of anti-reflection films and optical lenses.

[0003] For example, it is recorded in the literature (Macromolecules, 1991, 24 (25): 6660-6663) that fluorine-containing materials often have a lower refractive index. Therefore, fluorine-containing polymers with a specific structure can be used in the low refractive index layer of AR film. Patent No. CN116574208A discloses the use of metallocene catalysts to synthesize a series of cycloolefin copolymers of ethylene and fluorine-containing cycloolefin monomers. Although the material has a high fluorine content, its crystallization behavior is not conducive to the application of the material in the fields of anti-reflection films. It is well known that an increase in fluorine content will reduce the low refractive index of the material, but it also leads to a decrease in its surface energy, so that the interfacial adhesion with the adjacent high refractive index layer is reduced. At the same time, high fluorine-containing polymers are usually poorly soluble in cheap solvents that do not contain fluorine atoms, and often require special fluorine-containing solvents such as perfluorobenzene for dissolution, which directly leads to an increase in the production cost of the material.

[0004] Therefore, it is of great significance to develop an amorphous, ultra-low refractive index, highly transparent and highly fluorinated cyclic olefin copolymer. Summary of the invention

[0005] In view of the above technical problems, the present invention proposes a method for preparing an ultra-low refractive index and highly transparent cycloolefin copolymer.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention:

[0008] A fluorinated cyclic olefin copolymer, the general structural formula of which is shown in Formula I:

[0009]

[0010] Among them, A is selected from Any of;

[0011] 0.5≤y∶x≤19;

[0012] 0≤m≤1;

[0013] 1≤n≤4;

[0014] R1 is selected from any one of m1-m3, and the structures of m1-m3 are as follows:

[0015]

[0016] R2 and R3 are independently selected from any one of hydrogen, halogen, and C1-C10 perfluoroalkyl;

[0017] R4 and R5 are independently selected from any one of hydrogen, fluorine atom, and perfluoromethyl;

[0018] Among them, at least one group among R2, R3, R4 and R5 contains fluorine atoms.

[0019] Beneficial effects: The fluorinated cyclic olefin copolymer disclosed in the present invention has a high fluorine content (wt%). The high fluorine content and the random structure endow the fluorinated cyclic olefin copolymer with excellent physical properties such as a low refractive index, a high Abbe number, high transparency, and amorphous.

[0020] Preferably, the C1-C10 perfluoroalkyl group includes any one of a perfluoromethyl group, a perfluoroethyl group, a perfluoro-n-butyl group, a perfluoro-isopropyl group, a perfluoro-n-hexyl group, a perfluoro-n-octyl group and a perfluoro-n-decyl group.

[0021] Preferably, the structural formula of the fluorinated cyclic olefin copolymer includes:

[0022]

[0023] Preferably, the weight average molecular weight of the fluorinated cyclic olefin copolymer is (2-10)×10 4 g / mol; molecular weight distribution is 1.3~2.2.

[0024] The second technical solution of the present invention:

[0025] The preparation method of the fluorinated cyclic olefin copolymer comprises the following steps:

[0026] Under the conditions of Grubbs catalyst and organic solvent, a cycloolefin monomer and a fluorine-containing cycloolefin monomer undergo a ring-opening metathesis polymerization reaction to prepare an unsaturated fluorine-containing cycloolefin copolymer;

[0027] The unsaturated fluorinated cycloolefin copolymer and a hydrogen source are subjected to a hydrogenation reaction to obtain the fluorinated cycloolefin copolymer.

[0028] Preferably, the cycloolefin monomer comprises any one of the following structures of formula II,

[0029]

[0030] Preferably, the fluorinated cycloolefin monomer comprises any one of the following structures of formula III:

[0031]

[0032] Preferably, the organic solvent includes any one of dichloromethane, chloroform, tetrachloroethane, chlorobenzene, o-dichlorobenzene, trichlorobenzene, cyclohexane, methylcyclohexane, toluene and xylene; more preferably, it is one or more of dichloromethane, chloroform, tetrachloroethane, methylcyclohexane and chlorobenzene.

[0033] Preferably, the hydrogen source includes hydrazine compounds and high-purity hydrogen; more preferably, p-toluenesulfonyl hydrazide or high-purity hydrogen.

[0034] Preferably, the Grubbs catalyst is Cat.1 (Grubbs II, dichloro[1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinyl](3-methyl-2-butenyl)(tricyclohexylphosphine)ruthenium(II)) and / or Cat.2 (Grubbs III, dichloro[1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinyl](benzylidene)bis(3-bromopyridine)ruthenium(II)).

[0035] Beneficial effects: When the Grubbs II / III generation catalyst is used for ring-opening metathesis polymerization, the catalyst has excellent tolerance to polar groups, and exhibits excellent homopolymerization and copolymerization ability and high reactivity to fluorinated cycloolefin monomers. At the same time, under the premise of ring tension as the driving force for polymerization, the ring-opening metathesis polymerization copolymers obtained from the compounds having the structures of formula II and formula III are all amorphous structures, i.e., non-crystalline structures. This is crucial for applications in optical fields such as anti-reflection films.

[0036] Preferably, the conditions for the ring-opening metathesis polymerization reaction are:

[0037] React at 25°C for 120 min.

[0038] Preferably, the conditions of the hydrogenation reaction are:

[0039] Heat the reaction at 120-150°C for 6-16h.

[0040] The third technical solution of the present invention:

[0041] The fluorinated cycloolefin copolymer is used in preparing low refractive index optical lenses and anti-reflection coatings.

[0042] Compared with the prior art, the present invention has the following advantages and technical effects:

[0043] 1. Compared with the prior art, the present invention uses a highly tolerant Grubbs catalyst to design and synthesize a fluorinated cycloolefin copolymer having an amorphous structure, a high fluorine content, an ultra-low refractive index (the refractive index is adjustable between 1.37 and 1.47), high transparency and good solubility in conventional solvents.

[0044] 2. The polymer and monomer are both cyclic structures, the polymerization driving force is driven by the release of ring tension, and the random copolymerization properties of the catalyst synergistically achieve the synthesis of non-crystalline amorphous polymers.

[0045] 3. The introduction of non-fluorinated cycloolefin monomers into the polymer structure not only increases the solubility of the material in non-fluorinated solvents, but also effectively increases its compatibility with commercial cycloolefin copolymers COC and cycloolefin copolymers COP, which are pure cycloalkane structure products, thereby improving the interfacial adhesion between the anti-reflective coating and the substrate material. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0047] Figure 1 (a) is the H NMR spectrum obtained in Example 1 of the present invention; (b) is the H NMR spectrum obtained in Example 2 of the present invention;

[0048] Figure 2 (a), (b), (c), and (d) are the light transmittances of the fluorinated copolymers obtained in Example 3, Example 4, Example 5, and Example 10 of the present invention, respectively;

[0049] Figure 3 Wherein (a), (b), (c), and (d) are the refractive indices of the fluorinated copolymers obtained in Example 3, Example 11, Example 7, and Example 19 of the present invention, respectively;

[0050] Figure 4 (a), (b), and (c) are differential scanning calorimetry DSC curves of the fluorinated copolymers obtained in Example 4, Example 10, and Example 20, respectively;

[0051] Figure 5 (a), (b), and (c) are the tensile curves of the fluorinated copolymers obtained in Example 4, Example 5, and Example 8, respectively. DETAILED DESCRIPTION

[0052] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0053] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0054] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0055] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0056] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0057] The present invention discloses a fluorinated cyclic olefin copolymer having a structure of formula I:

[0058]

[0059] In formula I (I1, I2), x and y are the degree of polymerization, 0.5≤y:x≤19, 0≤m≤1,

[0060] R2 and R3 are independently selected from one or more of hydrogen, halogen, and C1-C10 perfluoroalkyl.

[0061] R4 and R5 are independently selected from any one of hydrogen, fluorine atom, and perfluoromethyl;

[0062] wherein at least one of R2, R3, R4, and R5 contains a fluorine atom;

[0063] In formula I1, 1≤n≤4, the structure on the left side of formula I1 is a non-cyclic straight-chain alkane structure;

[0064] In formula I2, the structure on the left side of formula I2 is a cyclic structure, wherein R1 is selected from any one of m1-m3, and the structures of m1-m3 are as follows:

[0065]

[0066] Among them, the carbon atom marked with * in m1-m3 is directly connected to the carbon atom corresponding to the carbon atom marked with * in the cycloolefin monomer via a carbon-carbon single bond.

[0067] In some preferred embodiments, the perfluoroalkyl group of C1-C10 includes perfluoroalkyl groups of C1, C2, C4, C6, C8, and C10, and further, preferably any one of perfluoromethyl, perfluoroethyl, perfluoro-n-butyl, perfluoroisopropyl, perfluoro-n-hexyl, perfluoro-n-octyl, and perfluoro-n-decyl.

[0068] In some preferred embodiments, the weight average molecular weight of the fluorinated copolymer is 2×10 4 g / mol-10×10 4 g / mol, more preferably 2×10 4 g / mol-8×10 4 g / mol.

[0069] In some preferred embodiments, the insertion rate of the above-mentioned fluorinated cycloolefin monomer can be adjusted between 5%-95%, that is, 0.052≤y∶x≤19; more preferably, 50%-95%, that is, 1≤y∶x≤19, and further preferably, 60%-90%, that is, 1.5≤y∶x≤9.

[0070] In some preferred embodiments, the fluorine content in the fluorine-containing copolymer of formula I is 20 wt%-64 wt%; more preferably 25 wt%-64 wt%, further preferably 30 wt%-64 wt%.

[0071] In addition, the present invention also provides a preparation process of a fluorinated cycloolefin copolymer, wherein the cycloolefin monomers of the structures shown in formula II and formula III and the fluorinated cycloolefin monomers are subjected to ring-opening metathesis polymerization under a Grubbs catalyst, and then subjected to a hydrogenation reaction with a hydrogen source to obtain a fluorinated cycloolefin copolymer having a structure shown in formula I;

[0072]

[0073] The process for preparing the above-mentioned fluorinated cycloolefin copolymer is as follows:

[0074] (1) Under the action of a Grubbs catalyst, a compound having a structure represented by Formula II and a compound having a structure represented by Formula III are subjected to a ring-opening metathesis polymerization reaction in a solvent to obtain an unsaturated fluorinated cycloolefin copolymer;

[0075] (2) hydrogenating the polymerization product and a hydrogen source to obtain a fluorinated cycloolefin copolymer having a structure as shown in Formula I;

[0076] In some preferred embodiments, the Grubbs catalyst is selected from Cat.1 (Grubbs II, dichloro[1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinylidene](3-methyl-2-butenylidene)(tricyclohexylphosphine)ruthenium(II)) and / or Cat.2 (Grubbs III, dichloro[1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinylidene](benzylidene)bis(3-bromopyridine)ruthenium(II));

[0077] The specific structure of Grubbs catalyst is as follows:

[0078]

[0079] In some preferred embodiments, the polymerization reaction solvent is a halogenated hydrocarbon compound, a halogenated aromatic hydrocarbon compound, a cycloalkane compound, or an aromatic hydrocarbon compound; more preferably, it is any one of dichloromethane, chloroform, tetrachloroethane, chlorobenzene, o-dichlorobenzene, trichlorobenzene, cyclohexane, methylcyclohexane, toluene, and xylene; further preferably, it is any one of dichloromethane, chloroform, tetrachloroethane, methylcyclohexane, and chlorobenzene.

[0080] In some preferred embodiments, the fluorinated cycloolefin monomers (III-1 to III-12) of the structure shown in Formula III include but are not limited to the following structures:

[0081]

[0082] The compounds having the structure shown in Formula II and the structure shown in Formula III used in the embodiments of the present invention can be prepared by existing literature or methods (e.g., Macromolecular Chemistry and Physics, 2016, 217(24): 2708-2716; or CN103965402A).

[0083] In the present invention, the compound having the structure shown in Formula III is prepared according to the following reaction route:

[0084]

[0085] Among them, the preferred range of R2-R5 is the same as above and will not be repeated here.

[0086] In some preferred embodiments, the molar ratio of cyclopentadiene to the substituted monoolefin is 1:(2-4); more preferably 1:(2.5-4);

[0087] The present invention has no particular limitation on the amount of the polymerization reaction solvent, and the amount of the solvent used in the polymerization reaction well known to those skilled in the art can be used.

[0088] In some preferred embodiments, in a 100 mL reactor, the volume of the polymerization reaction solvent is selected to be 35-60 mL, more preferably 40-50 mL, and the mass concentration of the total monomer feed amount is controlled at 1 wt% to 4 wt%.

[0089] In some preferred embodiments, after the polymerization reaction in step (1) is completed, the following steps are further included:

[0090] The polymerization reaction is terminated by using a small amount of vinyl ethyl ether to obtain a polymerization reaction solution; the polymerization reaction solution is mixed with ethanol to obtain a precipitated product; the precipitated product is filtered, washed and dried to obtain a polymerization reaction product.

[0091] In some preferred embodiments, the hydrogenation reaction is carried out under protective gas conditions; preferably nitrogen;

[0092] The hydrogen source includes hydrazine compounds and high-purity hydrogen gas; more preferably, it is p-toluenesulfonyl hydrazide or high-purity hydrogen gas.

[0093] In some preferred embodiments, after the hydrogenation reaction in step (2) is completed, the following steps are further included:

[0094] The obtained hydrogenation reaction product is mixed with a large amount of ethanol, and the obtained mixed product is filtered, washed and dried to obtain a hydrogenated fluorinated cycloolefin copolymer.

[0095] The structure and properties of the fluorinated cycloolefin copolymer obtained by the above preparation method are characterized, and the specific process is as follows:

[0096] The structure of the obtained fluorinated cycloolefin copolymer is characterized by nuclear magnetic hydrogen spectrum. The insertion rate of the fluorinated cycloolefin monomer is consistent with the monomer feed ratio. The fluorine content of the cycloolefin copolymer can be controlled at 30wt%-64wt%.

[0097] The present invention characterizes whether the obtained fluorinated cycloolefin copolymer has crystallization behavior by differential scanning calorimetry (DSC), and the fluorinated cycloolefin copolymer has no melting peak, which indicates that the fluorinated cycloolefin copolymer obtained by the present invention has an amorphous structure and has no crystallization behavior.

[0098] The invention characterizes the refractive index of the material by using an ellipsometer (SE-VE-L), and the refractive index of the prepared fluorinated cycloolefin copolymer can be adjusted between 1.37 and 1.47.

[0099] The mechanical properties of the fluorinated cycloolefin copolymer polymer material tested on the INSTRON 5969 instrument are tested according to the standard of GB / T1040-1992 "Test Method for Tensile Properties of Plastics".

[0100] The molecular weight of the fluorinated cycloolefin copolymer was characterized by GPC. The results showed that the weight average molecular weight of the prepared fluorinated copolymer was controlled within 2×10 4 g / mol~8×10 4 g / mol, and the molecular weight distribution is 1.3 to 2.2. The lower molecular weight effectively ensures the good solubility of the material in conventional solvents.

[0101] The invention uses a Shimadzu UV-3600 ultraviolet-visible-near infrared spectrophotometer to test the light transmittance and anti-reflection performance of the fluorinated cyclic olefin copolymer. The prepared cyclic olefin copolymer has a light transmittance of more than 92% in the visible light region (the test film thickness is 30 μm-50 μm), and the reflectivity is controlled below 1.5%.

[0102] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.

[0103] The "parts" described in the present invention, unless otherwise specified, refer to parts by mass.

[0104] The raw materials used in the present invention are all purchased from the market.

[0105] The technical solution of the present invention is further illustrated by the following embodiments.

[0106] Example 1

[0107] The preparation process of fluorinated cycloolefin monomer III (III-4) is shown in the following formula:

[0108]

[0109] To a 500 mL stainless steel autoclave, 19 g of cyclopentadiene and 180 g of III-1 fluorinated cycloolefin monomer were added in sequence. The autoclave was repeatedly evacuated and replaced with nitrogen for 3 times, and then filled with nitrogen at 1.5 MPa. The autoclave was deheated to 180°C, and the substances in the autoclave were reacted for 30 hours under stirring. After the autoclave was cooled to room temperature, it was distilled under reduced pressure at 40°C to collect excess III-1 monomer; then the residual liquid monomer was distilled under reduced pressure at 90°C, and the fractions were collected to obtain 50 g of the target product with a yield of 45.9%.

[0110] The above obtained product was subjected to nuclear magnetic resonance hydrogen spectrum detection. Figure 1 As can be seen from (a), the product obtained in Example 1 of the present invention is a compound having a structure shown in Formula III (III-4).

[0111] Example 2

[0112] The preparation process of fluorinated cycloolefin monomer III (III-5) is shown in the following formula:

[0113]

[0114] To a 500 mL stainless steel autoclave, 19 g of cyclopentadiene and 292 g of III-2 fluorinated cycloolefin monomer were added in sequence. The autoclave was repeatedly evacuated and replaced with nitrogen for 3 times, and then filled with nitrogen at 1.5 MPa. The autoclave was deheated to 180° C., and the substances in the autoclave were reacted for 30 hours under stirring. After the autoclave was cooled to room temperature, it was distilled under reduced pressure at 57° C. to collect excess III-2 monomer; then the residual liquid monomer was distilled under reduced pressure at 105° C., and the fractions were collected to obtain 68 g of the target product with a yield of 49.3%. The product was a white solid at room temperature.

[0115] The above obtained product was subjected to nuclear magnetic resonance hydrogen spectrum detection. Figure 1 As can be seen from (b), the target product obtained in Example 2 of the present invention is a compound having a structure shown in Formula III (III-5).

[0116] Example 3

[0117] A preparation process of a fluorinated cyclic olefin copolymer:

[0118] 1. Add 1.28 mmol (0.2058 g) of the compound having the structure shown in formula II (M4) and 1.93 mmol (0.7942 g) of the compound having the structure shown in formula III (III-2) to a dry polymerization reaction bottle at 25°C, add 45 mL of chloroform and stir for 5 minutes to fully dissolve. Then, under vigorous stirring, 23.7 mg of the catalyst Cat.2 was dissolved in 5 mL of chloroform solvent and added to the above polymerization reaction bottle for polymerization reaction at 25°C for 120 minutes;

[0119] 2. After the polymerization reaction time is over, 0.5 mL of vinyl ethyl ether is added to the above polymerization reaction bottle under stirring to quench the polymerization reaction, and then the above polymerization reaction solution is poured into anhydrous ethanol to obtain a precipitated product; the obtained precipitated product is filtered and washed with ethanol three times, and dried in a vacuum oven at 40°C for 12h to obtain 0.99g of a polymerization reaction product;

[0120] 3. In a dry pressure-resistant reaction bottle, add 0.9g of the above polymerization product, 2.69g (5eqv of unsaturated double bonds in the polymer) p-toluenesulfonyl hydrazide, 2.28g (5.5eqv of unsaturated double bonds in the polymer) tri-n-propylamine, 0.1g 2,6-di-tert-butyl-4-methylphenol (BHT) and 30mL of chloroform in sequence, and heat at 120°C for 16h to obtain a hydrogenation product; the hydrogenation product solution is added dropwise to 300mL of anhydrous ethanol for precipitation, and then the precipitate is redissolved in 20mL of chloroform at room temperature, and the above operation is repeated for washing twice. The obtained polymer is placed in a vacuum oven and dried at 60°C for 12h to obtain 0.85g of a saturated fluorinated cyclic olefin copolymer.

[0121] The weight average molecular weight of the fluorinated cycloolefin copolymer prepared in this example is 3.7×10 4 g / mol, molecular weight distribution 1.53. Fluorine content is 47.6wt%. Figure 2 (a) It can be seen that the transmittance of the fluorinated cycloolefin copolymer obtained in Example 3 of the present invention is >92% in the visible light region; Figure 3 (a) It can be seen that the refractive index of the fluorinated cyclic olefin copolymer obtained in Example 3 of the present invention is 1.42 (wavelength 589 nm); the reflectivity of the material is 0.9%; the polymer has an amorphous structure and no crystallization behavior is found.

[0122] Example 4

[0123] A preparation process of a fluorinated cyclic olefin copolymer:

[0124] 1. Add 1.37 mmol (0.2202 g) of the compound having the structure shown in formula II (M4) and 2.06 mmol (0.7798 g) of the compound having the structure shown in formula III (III-4) to a dry polymerization reaction bottle at 25°C, add 45 mL of dichloromethane and stir for 5 min to fully dissolve. Then, under vigorous stirring, 19.5 mg of the catalyst Cat.1 was dissolved in 5 mL of dichloromethane solvent and added to the above polymerization reaction bottle for polymerization reaction at 25°C for 120 min;

[0125] 2. After the polymerization reaction time is over, 0.5 mL of vinyl ethyl ether is added to the above polymerization reaction bottle under stirring to quench the polymerization reaction, and then the above polymerization reaction solution is poured into anhydrous ethanol to obtain a precipitated product; the obtained precipitated product is filtered and washed with ethanol three times, and dried in a vacuum oven at 40° C. for 12 h to obtain 0.98 g of a polymerization reaction product;

[0126] 3. The autoclave was vacuum dried at 110° C. for 6 h and then cooled to room temperature; 0.9 g of the polymer was completely dissolved using ultra-dry solvent tetrachloroethane, and then 10 wt % of Pd / C (0.033 g) catalyst was mixed with the polymer solution under a nitrogen atmosphere, and the mixed polymer solution was immediately introduced into the autoclave, and high-purity hydrogen gas of 5 MPa was introduced, and the reaction was carried out at 150° C. for 6 h to obtain a hydrogenation reaction product; the hydrogenation product solution was dropwise added to 300 mL of anhydrous ethanol for precipitation, and then the precipitate was redissolved in 20 mL of chloroform at room temperature, and the above operation was repeated for washing twice; the obtained polymer was placed in a vacuum oven and dried at 60° C. for 12 h to obtain 0.86 g of a saturated fluorinated cycloolefin copolymer.

[0127] The weight average molecular weight of the fluorinated cycloolefin copolymer prepared in this example is 4.4×10 4 g / mol, molecular weight distribution 1.65. Fluorine content is 35.2wt%. Figure 2 As shown in (b), the transmittance of the fluorinated cyclic olefin copolymer obtained in Example 4 of the present invention is >92% in the visible light region; the refractive index of the material is 1.46 (wavelength 589nm), and the reflectivity is 1.3%; Figure 4 From (a), it can be seen that the glass transition temperature of the fluorinated cycloolefin copolymer obtained in Example 4 is 149°C, and the polymer is amorphous and no crystallization behavior is found; Figure 5 From (a), it can be seen that the tensile strength of the fluorinated cycloolefin copolymer obtained in Example 4 is 59.5 MPa and the elongation at break is 10.1%.

[0128] Example 5

[0129] A preparation process of a fluorinated cyclic olefin copolymer:

[0130] 1. Add 1.27 mmol (0.2043 g) of the compound having the structure shown in formula II (M4) and 1.91 mmol (0.7957 g) of the compound having the structure shown in formula III (III-8) to a dry polymerization reaction bottle at 25°C, add 45 mL of chloroform and stir for 5 minutes to fully dissolve. Then, under vigorous stirring, 20.1 mg of the catalyst Cat.2 was dissolved in 5 mL of chloroform solvent and added to the above polymerization reaction bottle for polymerization reaction at 25°C for 120 minutes;

[0131] 2. After the polymerization reaction time is over, 0.5 mL of vinyl ethyl ether is added to the above polymerization reaction bottle under stirring to quench the polymerization reaction, and then the above polymerization reaction solution is poured into anhydrous ethanol to obtain a precipitated product; the obtained precipitated product is filtered and washed with ethanol three times, and dried in a vacuum oven at 40° C. for 12 h to obtain 0.98 g of a polymerization reaction product;

[0132] 3. In a dry pressure-resistant reaction bottle, 0.9 g of the above polymerization product, 2.88 g (5 eqv of the molar number of unsaturated double bonds in the polymer) of p-toluenesulfonyl hydrazide, 2.44 g (5.5 eqv of the molar number of unsaturated double bonds in the polymer) of tri-n-propylamine, 0.1 g of 2,6-di-tert-butyl-4-methylphenol (BHT) and 30 mL of chloroform were added in sequence, and heated at 120°C for 16 h to obtain a hydrogenation product; the hydrogenation product solution was added dropwise to 300 mL of anhydrous ethanol for precipitation, and then the precipitate was redissolved in 20 mL of chloroform at room temperature, and the above operation was repeated for washing twice; the obtained polymer was placed in a vacuum oven and dried at 60°C for 12 h to obtain 0.86 g of a saturated fluorinated cyclic olefin copolymer.

[0133] The weight average molecular weight of the fluorinated cycloolefin copolymer prepared in this example is 4.4×10 4 g / mol, molecular weight distribution 1.43. Fluorine content is 50.9wt%. Figure 2 As shown in (c), the transmittance of the fluorinated cyclic olefin copolymer obtained in Example 5 of the present invention is >92% in the visible light region; the refractive index of the material is 1.40 (wavelength 589nm), and the reflectivity is 0.8%; the polymer has an amorphous structure and no crystallization behavior is found; Figure 5 As can be seen from (b), the tensile strength of the fluorinated cycloolefin copolymer obtained in Example 5 is 51.3 MPa, and the elongation at break is 14.3%.

[0134] In Examples 6-20, different types of II (M1-M6) monomers are copolymerized with III monomers to prepare fluorinated cycloolefin copolymers.

[0135] Among them, the ROMP reaction and hydrogenation method of Examples 6-10 were carried out under the same conditions as in Example 3, and the total feeding amount of the monomers was controlled at 1g, except that the monomers of Formula II and Formula III were fed according to the molar ratio of the monomers in Table 1, and the amounts of the catalyst Cat.2 in Examples 6-10 were 28.7mg, 25.2mg, 29.9mg, 24.2mg, and 27.8mg, respectively; The ROMP reaction and hydrogenation method of Examples 11-15 were carried out under the same conditions as in Example 4, and the total feeding amount of the monomers was controlled at 1g, except that the monomers of Formula II and Formula III were fed according to the molar ratio of the monomers in Table 1 The molar ratio of monomer feed is carried out, and the amount of catalyst Cat.1 in Examples 11-15 is 22.5mg, 26.3mg, 28.0mg, 20.6mg, and 18.8mg respectively; the ROMP reaction and hydrogenation method of Examples 16-20 are carried out under the same conditions as Example 5, and the total amount of monomer feed is controlled at 1g, except that the monomer of Formula II and the monomer of Formula III are carried out according to the molar ratio of monomer feed in Table 1, and the amount of catalyst Cat.2 in Examples 16-20 is 25.6mg, 26.2mg, 23.8mg, 19.7mg, and 18.1mg respectively. The properties of the fluorinated polymers prepared in Examples 6-20 are shown in Table 1.

[0136] Table 1

[0137]

[0138]

[0139] Note: The refractive index of fluoropolymer materials in Table 1 is the value at a wavelength of 589nm; M w , PDI are the weight average molecular weight and molecular weight distribution of the polymer, respectively, measured by GPC in 1,2,4-trichlorobenzene at 150°C, relative to a polystyrene standard. The film thickness for the transmittance test is 30-50 μm. Figure 2 (d) is the light transmittance of the fluorinated copolymer obtained in Example 10 of the present invention. The light transmittance of the fluorinated cycloolefin copolymer obtained in Example 10 is >92% in the visible light region.

[0140] Figure 3 Where (a), (b), (c), and (d) are the refractive indices of the fluorinated copolymers obtained in Example 3, Example 11, Example 7, and Example 19 of the present invention, respectively; Figure 3 As shown in (b), the refractive index of the fluorinated copolymer obtained in Example 11 is 1.47 (wavelength 589 nm); Figure 3 As shown in (c), the refractive index of the fluorinated copolymer obtained in Example 7 is 1.38 (wavelength 589 nm); Figure 3As can be seen from (d), the refractive index of the fluorinated copolymer obtained in Example 19 is 1.43 (wavelength 589 nm).

[0141] Figure 4 (a), (b), and (c) are differential scanning calorimetry DSC curves of the fluorinated copolymers obtained in Example 4, Example 10, and Example 20, respectively; Figure 4 As shown in (b), the glass transition temperature of the fluorinated cycloolefin copolymer obtained in Example 10 is 161°C, and the polymer is amorphous and no crystallization behavior is found. Figure 4 As can be seen from (c), the glass transition temperature of the fluorinated cycloolefin copolymer obtained in Example 20 is 115°C, and the polymer has an amorphous structure without any crystallization behavior.

[0142] Figure 5 (a), (b), and (c) are the tensile curves of the fluorinated copolymers obtained in Example 4, Example 5, and Example 8, respectively. Figure 5 As shown in (c), the tensile strength of the fluorinated cycloolefin copolymer obtained in Example 8 is 58.3 MPa, and the elongation at break is 19.2%.

[0143] Conclusion: According to the data obtained in the examples of the present invention, it can be concluded that with the increase of fluorine content, the refractive index of the fluorine-containing polymer material tends to decrease, and the introduction of non-fluorinated cycloolefin monomers can improve the solubility of the fluorine-containing polymer.

[0144] Comparative Example 1

[0145] A homopolymerization experiment was conducted with III-8 monomer (63.9 wt%) having a high fluorine content in the monomer. 2.40 mmol (1 g) of the compound having the structure shown in formula III (III-8) was added to a dry polymerization reaction bottle at 25°C, and 45 mL of chloroform was stirred for 5 minutes to fully dissolve. Under vigorous stirring, 19.3 mg of the catalyst Cat.2 was dissolved in 5 mL of chloroform solvent and added to the above polymerization reaction bottle for 120 minutes of polymerization at 25°C. However, precipitation occurred at the initial stage of polymerization.

[0146] Effect verification

[0147] The fluorinated cycloolefin polymer obtained in Example 5 containing non-fluorinated cycloolefin monomers was compared with the fluorinated polymer obtained in Comparative Example 1 without non-fluorinated cycloolefin monomers through a scratch test. The coating of the fluorinated cycloolefin polymer obtained in Example 5 containing non-fluorinated cycloolefin monomers on the surface of commercial COC / COP sheets showed only slight coating peeling at the scratch tip under a critical load of 15N. The coating of the polymer obtained in Comparative Example 1 on the surface of commercial COC / COP sheets showed greater coating curling and peeling under the same applied force of 15N.

[0148] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A fluorinated cyclic olefin copolymer, characterized in that: The general structural formula is shown in Formula I: Among them, A is selected from Any of; 0.5≤y∶x≤19; 0≤m≤1; 1≤n≤4; R1 is selected from any one of m1-m3, and the structures of m1-m3 are as follows: R2 and R3 are independently selected from any one of hydrogen, halogen, and C1-C10 perfluoroalkyl; R4 and R5 are independently selected from any one of hydrogen, fluorine atom, and perfluoromethyl; Among them, at least one group among R2, R3, R4 and R5 contains fluorine atoms.

2. A fluorinated cyclic olefin copolymer according to claim 1, characterized in that: The C1-C10 perfluoroalkyl group includes any one of a perfluoromethyl group, a perfluoroethyl group, a perfluoro-n-butyl group, a perfluoro-isopropyl group, a perfluoro-n-hexyl group, a perfluoro-n-octyl group, and a perfluoro-n-decyl group.

3. A fluorinated cyclic olefin copolymer according to claim 1, characterized in that: The structural formula of the fluorinated cyclic olefin copolymer includes:

4. A fluorinated cyclic olefin copolymer according to claim 1, characterized in that: The weight average molecular weight of the fluorinated cycloolefin copolymer is (2-10)×10 4 g / mol; molecular weight distribution is 1.3~2.

2.

5. A method for preparing a fluorinated cyclic olefin copolymer, characterized in that: The following steps are involved: Under the conditions of Grubbs catalyst and organic solvent, a cycloolefin monomer and a fluorine-containing cycloolefin monomer undergo a ring-opening metathesis polymerization reaction to prepare an unsaturated fluorine-containing cycloolefin copolymer; The unsaturated fluorinated cyclic olefin copolymer and a hydrogen source are subjected to a hydrogenation reaction to obtain the fluorinated cyclic olefin copolymer according to any one of claims 1 to 4.

6. The method for preparing a fluorinated cyclic olefin copolymer according to claim 5, characterized in that: The cycloolefin monomer includes any one of the following structures of formula II, and / or The fluorinated cycloolefin monomer includes any one of the following structures of formula III, 7. The method for preparing a fluorinated cyclic olefin copolymer according to claim 5, characterized in that: The Grubbs catalyst is dichloro[1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinyl](3-methyl-2-butenyl)(tricyclohexylphosphine)ruthenium(II) and / or dichloro[1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinyl](benzylidene)bis(3-bromopyridine)ruthenium(II).

8. The method for preparing a fluorinated cyclic olefin copolymer according to claim 5, characterized in that: The organic solvent comprises one or more of dichloromethane, chloroform, tetrachloroethane, chlorobenzene, o-dichlorobenzene, trichlorobenzene, cyclohexane, methylcyclohexane, toluene or xylene; and / or The hydrogen source includes hydrazine compounds or high-purity hydrogen.

9. The method for preparing a fluorinated cyclic olefin copolymer according to claim 5, characterized in that: The conditions of the ring-opening metathesis polymerization reaction are: reacting at 25° C. for 120 min; and / or The conditions of the hydrogenation reaction are: heating the reaction at 120-150° C. for 6-16 hours.

10. Use of the fluorinated cyclic olefin copolymer according to any one of claims 1 to 4 in the preparation of low refractive index optical lenses and anti-reflection coatings.

Citation Information

Patent Citations

  • Cycloolefin copolymer and preparation method thereof

    CN103965402A

  • Fluorine-containing cycloolefin copolymer and preparation method thereof

    CN116574208A

  • Method for producing fluorine-containing polymer

    CN107207708A

  • Cycloolefin copolymer as well as preparation method and application thereof

    CN110669207A

  • Amorphous fluorine-containing polymer, composition containing amorphous fluorine-containing polymer, and preparation method and application of amorphous fluorine-containing polymer

    CN115368507A

Cited By

  • Fluorine-containing polyester compound with low refractive index as well as preparation method and application of fluorine-containing polyester compound

    CN121362323A